REHABILITATION OF COMBATANTS WITH CONSTANT PHYSIOLOGICAL STRESS (Physical Culture and Sport: Scientific Perspective, 2024)
The purpose of this article is to introduce Psychosemantics of Types of Military Stress of Combatants: we mean Constant physiological stress of combatants with Post-traumatic stress disorder; to show the stages and the mechanisms of rehabilitation of combatants with constant physiological stress. Methods of the research. The following theoretical methods of the research were used to solve the tasks formulated in the article: a categorical method, structural and functional methods, the methods of the analysis, systematization, modeling, generalization. The experimental method was the method of organizing empirical research. The results of the research. We proved, that psychological and physiological rehabilitation of combatants served such basic tasks, as: detection and diagnosis of mental disorders in military personnel; evacuation of combatants who have been psychologically traumatized from the battlefield; restoration of impaired (lost) mental functions; correction of self-awareness, self-esteem and well-being of combatants who received mental disorders and physical mutilations. Conclusions. We showed, that the following methods were widely used by psychologists and rehabilitation specialists of military units and unit commanders in the practice of psychological rehabilitation of combatants who had received combat mental trauma: autogenic techniques (performance of mental self-regulation techniques, self-training, meditation, etc.); physiological methods (deep sleep, rest, quality food, drinking a lot of water, shower, field bath); organizational means (establishing a clear regime of work and rest, involvement of servicemen into active combat training, service, preservation of military uniform); medication means (sedatives, tranquilizers, antidepressants, nootropics, psychostimulants, phytotherapy, vitamin therapy, etc.); psychotherapeutic techniques and methods (individual and group rational psychotherapy, music, library, art, nature therapy, etc.).
Keywords: psychological and physiological rehabilitation; constant physiological stress; psychosemantics of Types of Military Stress; combat mental trauma; correction of self-awareness